Plant-derived secondary metabolites as the main source of efflux pump inhibitors and methods for identification - Armel Jackson Seukep; Victor Kuete; Lutfun Nahar; Satyajit D. Sarker; Mingquan Guo (Elsevier, 2020)
The upsurge of multiple drug resistance (MDR) bacteria substantially diminishes the effectiveness of antibiotic arsenal and therefore intensifies the rate of therapeutic failure. The major factor in MDR is efflux pump-mediated resistance. A unique pump can make bacteria withstand a wide range of structurally diverse compounds. Therefore, their inhibition is a promising route to eliminate resistance phenomenon in bacteria. Phytochemicals are excellent alternatives as resistance-modifying agents. They can directly kill bacteria or interact with the crucial events of pathogenicity, thereby decreasing the ability of bacteria to develop resistance. Numerous botanicals display noteworthy efflux pumps inhibitory activities. Edible plants are of growing interest. Likewise, some plant families would be excellent sources of efflux pump inhibitors (EPIs) including Apocynaceae, Berberidaceae, Convolvulaceae, Cucurbitaceae, Fabaceae, Lamiaceae, and Zingiberaceae. Easily applicable methods for screening plant-derived EPIs include checkerboard synergy test, berberine uptake assay and ethidium bromide test. In silico high-throughput virtual detection can be evaluated as a criterion of excluding compounds with efflux substrate-like characteristics, thereby improving the selection process and extending the identification of EPIs. To ascertain the efflux activity inhibition, real-time PCR and quantitative mass spectrometry can be applied. This review emphasizes on efflux pumps and their roles in transmitting bacterial resistance and an update plant-derived EPIs and strategies for identification.